Emerging therapeutic potential of the iridoid molecule, asperuloside: A snapshot of its underlying molecular mechanisms. (5th January 2020) - Chan, Yinghan; Ng, Sin Wi; Xin Tan, Joycelin Zhu; Gupta, Gaurav; Tambuwala, Murtaza M.; Bakshi, Hamid A.; Dureja, Harish; Dua, Kamal; Ishaq, Muhammad; Caruso, Vanni; Chellappan, Dinesh Kumar
Abstract: Over the years, the attention of researchers in the field of modern drug discovery and development has become further intense on the identification of active compounds from plant sources and traditional remedies, as they exhibit higher therapeutic efficacies and improved toxicological profiles. Among the large diversity of plant extracts that have been discovered and explored for their potential therapeutic benefits, asperuloside, an iridoid glycoside, has been proven to provide promising effects as a therapeutic agent for several diseases. Although, this potent substance exists in several genera, it is primarily found in plants belonging to the genus Eucommia. Recent decades have seen a surge in the research on Asperuloside, making it one of the most studied natural products in the field of medicine and pharmacology. In this review, we have attempted to study the various reported mechanisms of asperuloside that form the basis of its wide spectrum of pharmacological activities. Highlights: Asperuloside have potent medicinal properties including antiobesity and anti-inflammatory. Asperuloside inhibited the increase in body weight and visceral fat weight. The anti-inflammatory mechanism of Asperuloside was demonstrated in LPS-induced RAW 264.7 cells. The anticancer activity of Asperuloside was comparable with antimycin A3 . Asperuloside also demonstrated moderate antibacterial effects on several known microbes.